Frequency-adaptive cancellation of harmonic disturbances at non-measurable positions of steel strips. (November 2020) - Marko, L.; Saxinger, M.; Steinboeck, A.; Kemmetmüller, W.; Kugi, A.
Abstract: The active rejection of harmonic disturbances is of great importance in many industrial applications. For instance, transverse vibrations of steel strips in hot-dip galvanizing lines entail an inhomogeneous zinc coating of the final product. Controlling the vibrations of these steel strips is particularly complicated because their direct measurement at the relevant location is not available. More specifically, the disturbance input, the displacement measurement, the electromagnetic actuator which acts as control input, and the system output to be controlled are all located at different positions along the steel strip. The control scheme proposed in this work minimizes the harmonic steady-state response of the system output to be controlled. In contrast to a state–space approach, the method does not utilize a high-dimensional state observer, and requires only modest computational resources during online operation. Furthermore, negative effects in the closed-loop system due to observation or control spillover are effectively avoided. The developed harmonic disturbance rejection scheme is validated by experiments conducted on a test rig that mimics the conditions from an industrial hot-dip galvanizing line.